DN interaction from meson exchange - Haidenbauer, J.; Krein, G. [UNESP]; Meißner, U. G.; Tolos, L. (Springer Nature, 2011)
A model of the DN interaction is presented which is developed in close analogy to the meson-exchange KN potential of the Jülich group utilizing SU(4) symmetry constraints. The main ingredients of the interaction are provided by vector meson (ρ, ω) exchange and higher-order box diagrams involving D *N, DΔ, and D *Δ intermediate states. The coupling of DN to the π Λ c and π Σ c channels is taken into account. The interaction model generates the Λ c(2595)-resonance dynamically as a DN quasi-bound state. Results for DN total and differential cross sections are presented and compared with predictions of two interaction models that are based on the leading-order Weinberg-Tomozawa term. Some features of the Λ c(2595)-resonance are discussed and the role of the near-by π Σ c threshold is emphasized. Selected predictions of the orginal KN model are reported too. Specifically, it is pointed out that the model generates two poles in the partial wave corresponding to the Λ(1405)-resonance. © 2011 SIF, Springer-Verlag Berlin Heidelberg.